Substituição parcial do fenol por lignina Kraft na síntese de resinas fenólicas - Xavier, Vitor Matheus Lagazzi (2021)
In recent years, there has been a worldwide interest in the development of "green" technologies which enable the use of products with less environmental impact. There is an increasing focus in the use of raw materials obtained from biomass. The interest increases, mainly, when the biomaterial comes from some industrial waste. From this motivation, there has been the replacement of phenol by lignin for the production of phenolic resins. The used lignin came from the industrial paper and cellulose waste and extracted through the Kraft process. The aiming was reducing the dependence on phenol, a petroleum derivative, by developing a more sustainable product and increasing the value of lignin once, currently, this biopolymer is burned in boilers for power generation. Thus, lignin was used as a partial substitute for phenol in the condensation reactions of phenolic resins of the resole type, to produce lignin-phenol-formaldehyde adhesives for wood which do not have the distillation step in the manufacturing process. In order to identify the best polymerization parameters and find the highest percentage of mass substitution (lignin for phenol), factorial design was used. The resulting model indicated that the best replacement conditions and condensation time were approximately 15% and 75 minutes, respectively. Meanwhile and aiming industrial interest, maximum replacement percentage and shorter condensation time (less time spent in the reactor batch), the system was also studied with 20% replacement and 55 minutes of condensation. The physical-chemical properties of the synthesized adhesives were assessed by viscosity, solids content, gelatinization time (gel time) and mechanical strength of glued joints techniques, comparing them with the standard sample (100% phenol used in its synthesis, that is, without replacement) and the replaced samples. The results achieved in the physical-chemical analyses and mechanical strength of glued joints tests of the modified resins were similar or superior when compared with the pure resin. Once we had an increase in pressing time or an increase of the press temperature, we could possibly have obtained better mechanical strength of glued joints results for the experiment with a higher replacement percentage. Through the obtained results by differential scanning calorimetry of the three tested samples, it was possible to observe peculiar endothermic peaks from the reticulation process, we could suggest that the higher the percentage of replacement the higher the energy will be required for the crosslinking of the lignin-phenol-formaldehyde polymer, due to displacement of the curves to higher temperatures. Finally, it was concluded that it is possible to replace phenol up to 20%, having the required properties as a phenolic adhesive maintained.